2019
DOI: 10.1016/j.brainres.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

The role of catecholamines in HIV neuropathogenesis

Abstract: The success of anti-retroviral therapy has improved the quality of life and lifespan of HIV + individuals, transforming HIV infection into a chronic condition. These improvements have come with a cost, as chronic HIV infection and long-term therapy have resulted in the emergence of a number of new pathologies. This includes a variety of the neuropathological and neurocognitive effects collectively known as HIVassociated neurocognitive disorders (HAND) or NeuroHIV. These effects persist even in the absence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 374 publications
(392 reference statements)
0
39
0
Order By: Relevance
“…Short-term morphine exposure significantly changed levels of the aromatic amino acids (i.e., having an aromatic side chain) phenylalanine and tyrosine in a CNS region-dependent manner. These findings are interesting considering the essential role of phenylalanine and its conversion to tyrosine in catecholamine synthesis [ 110 ] and bearing in mind the wide-spread alterations in catecholamines (i.e., dopamine, norepinephrine, and epinephrine) in neuroHIV [ 111 ]. Specifically, it has been shown that immune activation can lead to diminished conversion of phenylalanine to tyrosine as evidenced by a higher phenylalanine/tyrosine (P/T) ratio [ 112 ], which has been shown to be present in HIV-infected patients [ 113 ] and potentially contributes to the dopamine deficiency in people living with HIV [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term morphine exposure significantly changed levels of the aromatic amino acids (i.e., having an aromatic side chain) phenylalanine and tyrosine in a CNS region-dependent manner. These findings are interesting considering the essential role of phenylalanine and its conversion to tyrosine in catecholamine synthesis [ 110 ] and bearing in mind the wide-spread alterations in catecholamines (i.e., dopamine, norepinephrine, and epinephrine) in neuroHIV [ 111 ]. Specifically, it has been shown that immune activation can lead to diminished conversion of phenylalanine to tyrosine as evidenced by a higher phenylalanine/tyrosine (P/T) ratio [ 112 ], which has been shown to be present in HIV-infected patients [ 113 ] and potentially contributes to the dopamine deficiency in people living with HIV [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HIV Tat primes and activates proinflammatory responses in microglia via the NLR family pyrin domain containing 3 (NLRP3) inflammasome (Chivero et al, 2017), and dopamine can activate NF-κB and prime the NLRP3 inflammasome in macrophages (Nolan et al, 2020) (however, see Zhu et al, 2018). This could be exacerbated by drugs of abuse that promote dopamine transmission within areas of the brain that are particularly vulnerable to HIV, such as the striatum (Nolan and Gaskill, 2019). Clinically, the mitochondrial protein translocator protein (TSPO), which has garnered interest as a biomarker of neuroinflammation in human imaging studies (Werry et al, 2019), is upregulated in people living with HIV (PLWH) and increased TSPO within the hippocampus, amygdala, and thalamus is associated with impaired cognition (Vera et al, 2016).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…The high prevalence of frontal/ACC atrophy in HIV+ adults is likely due to multiple pathophysiological factors, including injury to the dopaminergic system. The frontal/ACC (especially the ACC) receives rich dopaminergic innervation as part of the mesocortical pathway that originates from dopaminergic neurons in the ventral tegmental area (Nolan & Gaskill, 2019), and studies have suggested that the mesocortical dopamine fibers projection to the prefrontal cortex and ACC is important for executive function, working memory, motivation, and emotion [Nolan & Gaskill, 2019]. Here we hypothesized that the injury to the dopaminergic system in HIV (Chang et al, 2008;Kumar et al, 2009;Nath et al, 2000) might have contributed to the high prevalence of frontal/ACC atrophy, as well as executive dysfunction (Heaton et al, 2010) and apathy (Paul et al, 2005;Walker & Brown, 2017) in HIV+ adults.…”
Section: The Frontal/acc Atrophymentioning
confidence: 99%